San Francisco: A Book of Numbers - Evanson, Ashley (Hello World, 2015)
Hello, World is an exciting board book series that pairs early learning concepts with colorful, stylish illustrations of cities around the world. From the Golden Gate Bridge to seals to the Painted Ladies, there's no shortage of bright, bold, and interesting things to count in San Francisco. Explore numbers through the best the city has to offer in this gorgeous board book!